2021
DOI: 10.3389/fphar.2021.713197
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of Fecal Microbiome and Metabolomics in Hepatic Fibrosis Rats Reveal Hepatoprotective Effects of Yinchen Wuling Powder From the Host-Microbial Metabolic Axis

Abstract: Hepatic fibrosis (HF) is a typical consequence in the development of multiple chronic liver diseases, which is intimately related to the composition and metabolic status of gut microbiota. A myriad of evidence has indicated that traditional Chinese medicine can treat HF by regulating gut microbiota. Yinchen Wuling powder (YCWLP) is a famous traditional Chinese medicine prescription, which has been used to relieve liver diseases for thousands of years. YCWLP has demonstrated protective function on HF, but its e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…The composition of HRG is Yinchen (YC), Juemingzi (JMZ), Dahuang (DH), Zexie (ZX), Zhuling (ZL), Shanzha (SZ), Cangzhu (CZ), Baizhu (BZ), Chenpi (CP), Gualou (GL), Nvzhenzi (NZZ), Mohanlian (MHL), Gouqizi (GQZ), Xiaoji (XJ), Chaihu (CH), Gancao (GC). Studies have shown that this formula can not only improve lipid deposition in the liver, protect liver cell membranes and reduce liver damage but also protect the intestinal barrier and regulate intestinal flora ( Niu et al, 2011 ; Chen et al, 2015 ; Gao et al, 2021 ; Zhang et al, 2021 ; Zhang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The composition of HRG is Yinchen (YC), Juemingzi (JMZ), Dahuang (DH), Zexie (ZX), Zhuling (ZL), Shanzha (SZ), Cangzhu (CZ), Baizhu (BZ), Chenpi (CP), Gualou (GL), Nvzhenzi (NZZ), Mohanlian (MHL), Gouqizi (GQZ), Xiaoji (XJ), Chaihu (CH), Gancao (GC). Studies have shown that this formula can not only improve lipid deposition in the liver, protect liver cell membranes and reduce liver damage but also protect the intestinal barrier and regulate intestinal flora ( Niu et al, 2011 ; Chen et al, 2015 ; Gao et al, 2021 ; Zhang et al, 2021 ; Zhang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Pseudo germ-free (PGF) rats were established by giving broad-spectrum antibiotics to explore whether SGD can treat the liver injury by regulating gut microbiotas. Broad-spectrum antibiotics contain cefadroxil (100 mg/kg), neomycin sulfate (300 mg/kg) and erythromycin (300 mg/kg) ( Zhang et al, 2021a ).…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, other groups were given the same amount of water. Record the weight of rats every week ( Zhang et al, 2021a ).…”
Section: Methodsmentioning
confidence: 99%
“…Ingredient modifications of these formulas were performed based on clinically specific symptoms: Ginger pinellia and Bamboo shavings are added for Jaundice; Polygonum cuspidatum is added for those trapped by damp-evil. Yinchen Wuling Powder shows hepatoprotective effects by regulating the imbalance of the gut microbiota and increasing the abundance of butyrate-producing bacteria to regulate pro-inflammatory cytokines and immune function [ 148 ].…”
Section: Non-pharmacological Treatment Of Nafld In Western Medicinementioning
confidence: 99%